Judge's Considerations in the Case of Claims for Property Rights Certificates which have been Canceled Without the Knowledge of the Legal Owners at the Tanjungkarang District Court (Decision Study Number: 101/Pdt.G/2021/PN.Tjk) - Zulfi Diane Zaini; Yulia Hesti; Hemi Rianto (CV. Rayyan Dwi Bharata, 2023)
Land is the surface of the earth while land rights are rights over a certain portion of the earth's surface which is bounded, has two dimensions with length and width. The factors causing the lawsuit for the Property Rights Certificate which was canceled without the knowledge of the legal owner at the Tanjungkarang District Court Study of Decision Number 101/Pdt.G/2021/Pn Tjk, there are 3 main factors namely: the factor of unlawful acts committed by the Defendants, Factors the two Plaintiffs suffered losses in the form of material and immaterial losses, and the last factor was the existence of a causal relationship between the parties in which the co-defendant had deliberately issued SHM No. 511 which still contains an ownership dispute between the Defendant and the Plaintiff. The consideration of the panel of judges in the lawsuit for a Property Rights Certificate which was canceled without the knowledge of the legal owner at the Tanjungkarang District Court Study of Decision Number 101/Pdt.G/2021/Pn Tjk is that the Plaintiff's lawsuit has not can be used as a reference for the Panel of Judges to examine the lawsuit material because there is still a shortage of parties in this case.